2012
DOI: 10.3390/polym4031331
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Crystallinity of Electrospun Plla Fibres by Control of Electrospinning Parameters

Abstract: Poly(L-lactic acid) (PLLA) fibers were fabricated by electrospinning. The effects of various electrospinning process parameters on the thermal properties, especially the crystallinity of the electrospun fibers were investigated. Thermal analysis of the fibers revealed that they exhibited degree of crystallinity ranging from 23% to 46% while that for the as-received granules was approximately 37%, suggesting that the crystallinity of electrospun PLLA fibres can be controlled by optimizing the electrospinning pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 49 publications
2
61
0
Order By: Relevance
“…Observed decreases in degree of crystallinity at higher concentration of TNR might be due to the poor dispersion and subsequent agglomeration of TNR in PCL, which disturb the crystallization process. Decrease in overall crystallinity of polymers affects the tensile strength, and the results of tensile results agree with this . Earlier studies also showed that crystallinity of PCL decreases with the addition of higher quantity (above 2% w/w) of nanoparticles such as ZnO in polymer matrix which can be due to the agglomeration of nanoparticles at higher concentration …”
Section: Resultssupporting
confidence: 66%
“…Observed decreases in degree of crystallinity at higher concentration of TNR might be due to the poor dispersion and subsequent agglomeration of TNR in PCL, which disturb the crystallization process. Decrease in overall crystallinity of polymers affects the tensile strength, and the results of tensile results agree with this . Earlier studies also showed that crystallinity of PCL decreases with the addition of higher quantity (above 2% w/w) of nanoparticles such as ZnO in polymer matrix which can be due to the agglomeration of nanoparticles at higher concentration …”
Section: Resultssupporting
confidence: 66%
“…One of the possible reasons is related to the effect of crystallinity on the degradation kinetics [31].…”
Section: Introductionmentioning
confidence: 99%
“…As such, it can be concluded that the observed changes in crystalline structure of the PLA nanofibers after PEPT are indeed not an effect of the performed PEPT but are the results of the electrospinning process. Other research groups have also already observed an effect of the electrospinning process on the crystalline structure of the resultant electrospun nanofibers, which can be tuned by adjusting the used electrospinning parameters …”
Section: Resultsmentioning
confidence: 99%